Counter-argumentation and anaphoric substitution: the role of the Spanish connective a pesar de ello - Guillén Jiménez, Luis Diego (Sprache - Gesellschaft - Geschichte, 2023)
"This book presents an experimental study using eye-tracking methods and experimental pragmatics to examine the role of the Spanish connective a pesar de ello in the recovery of counter-argumentative and anaphoric relations. The book analyzes the processing patterns triggered by the connective when establishing such relations and how these are affected by the position of the connective, the recovery of conflictive assumptions, and the extension and complexity of the antecedent. The results shed light on the limits of the procedural instruction of a pesar de ello as affected by its level of grammaticalization and explicit anaphoric instruction. Overall, the book contributes to a general characterization of the principles underlying the instructions displayed by discourse markers."--Back cover
Includes bibliographical references
Dissertation eingereicht unter dem Titel: "Experimental analysis of the processing schemas of counter-argumentation and anaphoric substitution signaled by the Spanish connective a pesar de ello"
Keywords: Hochschulschrift; a pesar de ello; Logische Partikel; Spanisch